GROWTH PERFORMANCE, HEMATOLOGICAL AND HISTOLOGICAL PARAMETERS OF NILE TILAPIA LARVAE FED DIETS SUPPLEMENTED WITH B-GLUCANES AND NUCLEOTIDES - Lopes de Melo, Caroline; Carvalho, Imaculada; Tank Fortunato, Murilo Henrique; Santana Natel, Andressa; do Nascimento, Ariane Flávia; Mattos Pedreira, Marcelo; Ferreira Menezes, Williane; Santos Amorim, Matheus Philip; Albers Koch, João Fernando (Acta Biologica Brasiliensia, 2024)
Food additives such as nucleotides and ?-glucans are used to enhance the performance and immunity of aquatic organisms. This study aimed to evaluate the addition of these substances in the diet of Nile tilapia larvae, assessing growth, survival, hematological parameters, histological changes, and stress resistance. The experiment lasted 30 days, with 800 larvae distributed across 16 aquariums and divided into four treatments: control (no supplementation), ?-glucan (0.75 g kg-1), nucleotide (2 g kg-1), and ?-glucan + nucleotide (0.75 + 2 g kg-1). The larvae fed diets supplemented with ?-glucan showed higher final weight, daily weight gain, total length, and specific growth rate, and better performance in the hypoxia test. Larvae fed the combination of ?-glucan + nucleotides also differed from the control for the same parameters, except for length. After stress challenges with salinity and hypoxia, larvae in the control group showed lower survival, demonstrating that the supplementation of ?-glucan and nucleotides improves stress resistance and animal well-being. Intestinal villus thickness was reduced in the nucleotide-supplemented diet. In conclusion, the supplementation of ?-glucan and nucleotides has positive effects on the survival and performance of Nile tilapia larvae, particularly under stress conditions.